2015
DOI: 10.18393/ejss.2015.4.266-271
|View full text |Cite
|
Sign up to set email alerts
|

Effects of organic and inorganic amendments on soil erodibility

Abstract: Article Info Received : 11.10.2014 Accepted : 27.04.2015 The objective of the present investigation is to find out the effect of incorporating of various organic and inorganic matter sources such as lime (L), zeolit (Z), polyacrylamide (PAM) and biosolid (BS) on the instability index. A bulk surface (0-20 cm depth) soil sample was taken from Samsun, in northern part of Turkey. Some soil properties were determined as follows; fine in texture, modarete in organic matter content, low in pH and free of alkaline p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…The climatic and geographical features of the Maritsa Basin cause frequent floods and heavy soil erosion [37]. Soil erosion by water threatens both agriculture and the natural environment by causing land degradation over time [38,39]. Erosion is a natural phenomenon causing environmental and economic consequences in the Eastern Europe and Balkan Peninsula, as well.…”
Section: Study Areamentioning
confidence: 99%
“…The climatic and geographical features of the Maritsa Basin cause frequent floods and heavy soil erosion [37]. Soil erosion by water threatens both agriculture and the natural environment by causing land degradation over time [38,39]. Erosion is a natural phenomenon causing environmental and economic consequences in the Eastern Europe and Balkan Peninsula, as well.…”
Section: Study Areamentioning
confidence: 99%
“…Lime application, in the form of slaked lime [Ca(OH) 2 ] and in a mixed form consisting of a blend of slaked lime [Ca (OH) 2 ] and calcium carbonate [CaCO 3 ], has been found to enhance the stability of aggregates in clayey soils (Blomquist et al 2017). The few studies that have assessed the effect of amendments on soil erodibility have not measured it directly, but rather have calculated erodibility based on its relation with other variables (Castro and Logan 1991;Ekwue 1992;Nishimura et al 2005;Özdemir et al 2015;Kumar et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the erosion rates of the soil samples were found to have significantly positive correlations with the dispersion rate (0.622**) and K factor (0.653**) values, which are the parameters used in assessing structural stability, at 1% level, and significantly negative correlation with aggregate stability (-0.546**) at 1% level (Table 2). Different researchers have obtained similar findings in their studies in different regions (García-Orenes et.al., 2009;Özdemir et al, 2015;Saygın et al, 2017). Gülser (2004) found that cropping treatments improved infiltration ratio by increasing sructural stability and porosity that can lead to the benefits of reduced erosion and improved soil water storage.…”
Section: Results Discussionmentioning
confidence: 99%